Study on Biology of Macrosiphum Avenae (Fabricious) (Homoptera; Aphidiade) at Kirtipur - Mahato, Shyam Prasad (Tribhuvan University Journal, 2011)
Not available. Key words: Aphids; Homopteran insects; Honey tubes; Nepal; Kirtipur Tribhuvan University Journal Vol XXI, No. 2, 1998 Page: 109-114 Uploaded date: 29 April, 2011